-5 + (5 + 3)

in the box below, show each step in simplifying the expression and explain which property you used in each step.

i already have

-5 + 5 + 3

5 + 3 = 8:

8 - 5

8 - 5 = 3

3

but i need to know what properties are used in this answer.

This is 6th grade math. lucky for you i'm a 7th grader the answer is: 3

HOW:

5+3=8

8+(-5)=3

BOOM

HOW:

5+3=8

8+(-5)=3

BOOM

Solve the parenthesis. (5+3) is 8. so the problem is simplified to -5+8. and the answer to that is 3

Number Properties: PEMDAS

Parentheses, Exponents, Multiplication, Division, Addition, & Subtraction

1. Parentheses

There Are No Exponents, Multiplication, Division, Or Addition

2. Subtraction

Parentheses, Exponents, Multiplication, Division, Addition, & Subtraction

1. Parentheses

There Are No Exponents, Multiplication, Division, Or Addition

2. Subtraction

I would say pemdas

Parenthesis

Exponents

Multiply

Divide

Addition

Subtract

Do the parenthesis first and then add negative five

You would do 5+3 which will equal 8

-5+8

8-5

The answer is 3 hope this helps

3

Step-by-step explanation:

so use PEMDAS for this, you always do parenthesis first so (5+3) = 8+-5= 3

–5 + (5 + 3) = 3

Solution:

Given expression is –5 + (5 + 3).

Using commutative property of addition: a + b = b + a

–5 + (5 + 3) = –5 + (3 + 5)

Using closure property of addition: a + b = c, any number.

–5 + (3 + 5) = –5 + 8

Using commutative property of addition: a + b = b + a

–5 + 8 = 8 – 5

Using closure property of addition: a + b = c, any number.

8 – 5 = 3

–5 + (5 + 3) = 3

Hence –5 + (5 + 3) = 3.

can i see the following ? step-by-step explanation:...Read More

1 more answers

dude thats to long figure it step-by-step explanation:...Read More

1 more answers

. + λrh() e 1 1 2 4 4 4 4 4 3 4 4 4 4 4 + th−1(− s(x)2 dx ω + λrh−1() e 2 1 2 4 4 step-by-step explanation:...Read More

1 more answers

Step-by-step explanation:The area of initial triangle and the area of reflected triangle are the same, soFind the area of triangle ABC using formulaIn triangle ABC:base = AC = 4 un...Read More

3 more answers

What is the last question i don’t see it?...Read More

2 more answers

justification 2 is incorrect.step-by-step explanation: since δabc is right angled at b, therefore by pythagoras theorem[tex]ab^2 + bc^2 = ac^2[/tex]we know that if two angles are...Read More

1 more answers

- PLEASE ANSWER ASAP PLEASE WILL MARK BRAINLIEST...
- A and b are complementary angles, a measures 44, what is the measure o...
- Factor 4x^2-13x+3 My teacher said to find the terms that would both a...
- Find the root(s) of f(x) = (x + 5)2(x - 9)2(x + 1). -5 with multiplic...
- 1) _ is caused by the weight of air above an area. * atmospheric pres...
- Please help . Don’t understand this math problem...
- In Exercises 1–4, use these results from a USA Today survey in which 5...
- The algebra teacher said if you square my age then subtract 23 times m...
- Define the term perpendicular...
- You are selling pizzas to raise money for a school field trip. Cheese...